Challenges in Teaching Aeronautical Software Quality Standards RTCA DO-178C and RTCA DO-200B - Marques, Johnny; Yelisetty, Sarasuaty (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
Teaching aeronautical software quality standards, such as RTCA DO-178C and RTCA DO-200B, presents significant challenges, mainly when delivered to students who do not work directly in this domain. This paper explores the complex characteristics of conveying these specialized standards to a diverse audience. We identify the primary challenges in the teaching-learning process through a detailed analysis of the difficulties faced. These challenges include the need to contextualize aeronautical quality standards with practical examples, the abstract nature of the content, and the necessity for interactive methods and teaching resources to facilitate comprehension. This study provides insights for educators and educational institutions to improve their approaches to teaching aeronautical software quality standards.